Legalization and Human Capital Accumulation - Sepulveda-Pizarro, F (Springer New York LLC, 2016)
This paper presents new evidence regarding the effects of legalization on the training of immigrants who were granted legal status through the US Immigration Reform and Control Act (IRCA) of 1986. Our findings point to a large increase in the immigrants’ incidence of training relative to comparable groups of natives following legalization. While training gains are higher for males, wage gains are higher for females. We also show that an important part of these changes in labor market outcomes occurs through occupation changes by newly legalized immigrants. © 2016, Springer-Verlag Berlin Heidelberg.